One-year Success Story—Rare Tillaux–Chaput Fracture Treated with Distal Radius T-plate Fixation: A Case Report - Elangovan Srinivas; Thirupathy V Raja (Journal of Foot and Ankle Surgery (Asia Pacific))
Aim and background: Tillaux–Chaput fractures are rare in adults and typically occur due to high-impact injuries. Accurate diagnosis often requires advanced imaging techniques, as standard radiographs may miss these fractures. This case report presents a 37-year-old patient with a Tillaux–Chaput fracture treated successfully with a distal radius T-plate fixation. Case description: A 37-year-old male presented with a swollen and tender ankle following a road traffic accident. Initial radiographs revealed an anterolateral ankle fracture, confirmed by computed tomography (CT) with 3D reconstruction. An open reduction and internal fixation (ORIF) was performed using a distal radius T-plate through an anterolateral Böhler type approach. The patient’s postoperative recovery was uneventful, with full ankle mobility and excellent functional scores [American Orthopedic Foot and Ankle Society Score (AOFAS) 98, foot and ankle ability measure (FAAM) 98%] at the 1-year follow-up. Conclusion: Tillaux–Chaput fractures in adults require careful evaluation and advanced imaging for accurate diagnosis. ORIF with a distal radius T-plate provides effective fixation and excellent functional recovery in cases with significant fragment displacement. Clinical significance: This case highlights the importance of tailored surgical approaches and comprehensive postoperative care in managing rare Tillaux–Chaput fractures in adults. The successful outcome demonstrates that advanced imaging and appropriate surgical intervention are critical for optimal recovery.